Stakeholder research in managing the Mount Hamiding Protected Forest in North Maluku Province - Kailola, Jacob (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2024)
Mount Hamiding Protected Forest in North Maluku Province has the potential with sufficient biodiversity available, However, management is not optimal so it needs to involve stakeholders The in forest management to achieve management goals, namely sustainable forests and prosperous communities. This research aims to identify and Identify parties involved in protected forest management. The methods employed are surveys and interviews. Data was assessed through stakeholder analysis. The research results show that the stakeholders involved in HLGH management cannot carry out their roles and functions optimally. Mapping stakeholders included in the key player position are KPH North Halmahera, BPDAS Akemalamo and North Maluku Forestry Service, subject positions are Bappeda North Halmahera Regency and Soakonora village. Crowd positions are Regional Stabilization and Environmental Management Center, Natural Resources Conservation Center, Food Crops and Horticulture Agriculture Service, North Halmahera Regency Tourism Office, Wahana Visi Indonesia Non-Governmental Organization, Halmahera University, Roko village, Togawa village, Wangongira village, Mamuya village and Efi-Efi. The position of context setter is North Maluku Province Bappeda, Social Forestry and Environmental Partnership Center. Contact between stakeholders is currently limited to coordination and communication; they don't have a cooperative relationship yet, Thus, it is required to create a cooperative partnership that fosters sustainable management of protected forests and increases the welfare of communities inhabiting the forest and its environs.